A non-coaxial theory of plasticity for soils with an anisotropic yield criterion - Yuan, Ran (2015)
A novel, non-coaxial soil model is developed in the context of perfect plasticity for the plane strain condition whilst incorporating initial soil strength anisotropy. The anisotropic yield criterion is developed by generalising the conventional isotropic Mohr-Coulomb yield criterion to account for the effects of initial soil strength anisotropy described by the variation of internal friction angles at different principal stress directions. The model is implemented into the commercial finite element(FE)software ABAQUS via the user defined material subroutine(UMAT).